2021
DOI: 10.3389/fonc.2021.770565
|View full text |Cite
|
Sign up to set email alerts
|

AQP9 Is a Prognostic Factor for Kidney Cancer and a Promising Indicator for M2 TAM Polarization and CD8+ T-Cell Recruitment

Abstract: BackgroundIt is undeniable that the tumor microenvironment (TME) plays an indispensable role in the progression of kidney renal clear cell carcinoma (KIRC). However, the precise mechanism of activities in TME is still unclear.Methods and ResultsUsing the CIBERSORT and ESTIMATE calculation methods, the scores of the two main fractions of tumor-infiltrating immune cells (TICs) from The Cancer Genome Atlas (TCGA) database of 537 KIRC patients were calculated. Subsequently, differentially expressed genes (DEGs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…In addition, JIng JB et al showed that the protein expression level of AQP9 was significantly increased in ccRCC, the expression level of AQP9 increased with the pathological stage of the tumor. At the same time, AQP9 was associated with the expression of macrophages and the inhibition of the recruitment of NK and CD8+T cells in the tumor microenvironment [56]. These experimental results can further confirm our results.…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, JIng JB et al showed that the protein expression level of AQP9 was significantly increased in ccRCC, the expression level of AQP9 increased with the pathological stage of the tumor. At the same time, AQP9 was associated with the expression of macrophages and the inhibition of the recruitment of NK and CD8+T cells in the tumor microenvironment [56]. These experimental results can further confirm our results.…”
Section: Plos Onesupporting
confidence: 89%
“…Jing JB et al explored the expression of AQP9 which was consistent with ours, and they also analyzed the relationship between AQP9 and tumor environment. The results showed that in ccRCC, AQP9 promoted tumor-associated macrophage polarization, inhibited the recruitment of natural killer (NK) cells and CD8+ T cells by inhibiting P53 and activating the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway, and ultimately stimulated a reorientation of the tumor microenvironment in ccRCC toward tumor-friendly directions [56]. Combining the above analyses of AQP1 and AQP9, we may guess that AQP1 is the tumor suppressor gene of ccRCC while AQP9 is the proto-oncogene of ccRCC.…”
Section: Plos Onementioning
confidence: 99%
“…Overall, the expression of AQP9 in humans appears to be more selective than in mice, with hepatocytes and neutrophils being by far the major expression sites in normal human tissues. Through the use of Aqp9 -KO cells, AQP9 protein expression has been verified in hepatocytes [ 53 , 77 , 78 , 79 ], immune cells, including neutrophils [ 80 , 81 ], macrophages [ 82 ], CD8+ T-cells [ 83 , 84 ], stratum granulosum of the epidermis [ 75 ], principal cells of the epididymis, and vas deferens [ 77 ], bone marrow dendritic cells [ 37 ], and a limited population of neuronal cells [ 58 , 76 , 85 ].…”
Section: Tissue Distributionmentioning
confidence: 99%
“…In macrophages, AQP9 was shown to be required in phagocytosis promoted by the Pseudomonas aeruginosa lasI/rhlI quorum sensing genes as its expression was strongly increased and the related protein was redistributed to the leading and trailing regions after macrophages were infected with the pathogen [ 82 ]. Involvement of AQP9 in macrophage M2 polarization has been recently shown in the progression of kidney renal clear cell carcinoma [ 84 ]. In CD8+ T cells, AQP9 was required for longevity and fast response to rechallenge [ 83 ], and to cell locomotion in reaching the tumor microenvironment [ 84 ].…”
Section: Physiological Roles and Regulationmentioning
confidence: 99%
See 1 more Smart Citation